Fludeoxyglucose positron emission tomography-computed tomography scan showing polyarthritis in a patient with an atypical presentation of Henoch-Schönlein vasculitis without clinical signs of arthritis: a case report. (December 2016) - Mooij, Christiaan; Hermsen, Rick; Hoppenreijs, Esther; Bleeker-Rovers, Chantal; IJland, Marloes; de Geus-Oei, Lioe-Fee
Abstract Background Henoch-Schönlein vasculitis is the most common systemic vasculitis in children. Arthritis or arthralgia occurs in 80 % of patients. We believe this to be the first case report to describe the finding of polyarthritis in a fludeoxyglucose positron emission tomography-computed tomography scan in a patient with Henoch-Schönlein vasculitis without clinical signs of arthritis. Case presentation A 4.5-year-old Caucasian boy presented with fever of 4 days' duration followed by debilitating migratory arthralgia and inflammation. He underwent a fludeoxyglucose positron emission tomography-computed tomography scan to exclude a possible malignant cause or to detect any infectious or autoimmune focus of his symptoms. Fludeoxyglucose uptake was observed in multiple large joints and in multiple tendons. These findings suggested active polyarthritis and polytendinitis. However, physical and ultrasound evaluations did not show any signs of arthritis in our patient, despite his evident arthralgia. Conclusions Fludeoxyglucose positron emission tomography-computed tomography might be able to detect inflammatory activity in painful joints that cannot yet be detected clinically or with ultrasound evaluation in a patient with Henoch-Schönlein vasculitis. Therefore, fludeoxyglucose positron emission tomography-computed tomography can be of additional value in the diagnostic workup of patients with an unresolved diagnosis of suspected autoimmune disease, especially in patients with unresolved arthralgia and fever of unknown cause.